Porabskoslovensko óvca ’osa’. Praslovanska sinonima *(v)osva : *(v)osa v slovenščini - Furlan, Metka (Slavia Centralis, 2020)
Slovene dialectal óvca ’wasp’ (Porabje). Proto-Slavic synomyms *(v)osva : *(v)osa in Slovene In a Slovene dialect óvca ’wasp’ (Porabje) the PSlav. *(v)osva ’idem’ is preserved. This Proto-Slavic word was homonymous with and related to the PSlav. *(v)osa > Sln. ósa.